Molecular Marker Approach In Honey Bee: A Review - BHARAT NEEKHRA,; DIVYA PANDEY,; MEETA MISHRA,; SUBODH KUMAR JAIN, (International Journal of Pharma and Bio Sciences, 2012)
The Honey bee is an important model animal for behavioral study as it is a colonial insect with complex social behavior. Many studies have characterized its fascinating behavioral repatriate, but little is known about the genetic basis of its behavior because of difficulties in maintaining selected stocks and the scarify of genetic markers. However, it is now possible to construct detailed linkage maps for insects by following the molecular markers segregation. Molecular markers analysis and genetic mapping are valuable tools for identifying chromosomal regions affecting behavioral traits. DNA markers have contributed significantly for understanding genetic basis of diversity, mapping medically and agriculturally important genes and quantitative trait loci (QTLs) in Honey bee. Molecular markers are used to infer phylogeny and biogeography of insect population and to understand modes of evolution and evolutionary trajectories. DNA markers such as mtDNA, RAPD, AFLP, microsatellite and ESTs are used as popular marker systems in honey bee genetic research. Although there are inherent advantages and disadvantages associated with each marker system, the choice of applying them depends upon the objectives of the study. The present review put light on genetic linkage mapping, quantitative trait loci analysis, behavior analysis, phylogenetic analysis, mitochondrial DNA markers, RAPD study, genetic variation and population study in honeybee.